Tunable TiO2–BN–Pd nanofibers by combining electrospinning and atomic layer deposition to enhance photodegradation of acetaminophen. Issue 7 (28th January 2022) - Sayegh, Syreina; Tanos, Fida; Nada, Amr; Lesage, Geoffroy; Zaviska, François; Petit, Eddy; Rouessac, Vincent; Iatsunskyi, Igor; Coy, Emerson; Viter, Roman; Damberga, Daina; Weber, Matthieu; et al.
Abstract : TiO2 –BN–Pd materials were successfully prepared by combining electrospinning and atomic layer deposition. The obtained materials show outstanding properties for the degradation of acetaminophen (ACT) under UV and visible light as well as high stability and recyclability. Abstract : The demand for fresh and clean water sources is increasing globally, and there is a need to develop novel routes to eliminate micropollutants and other harmful species from water. Photocatalysis is a promising alternative green technology that has shown great performance in the degradation of persistent pollutants. Titanium dioxide is the most used catalyst owing to its attractive physico-chemical properties, but this semiconductor presents limitations in the photocatalysis process due to the high band gap and the fast recombination of the photogenerated carriers. Herein, a novel photocatalyst has been developed, based on titanium dioxide nanofibers (TiO2 NFs) synthesized by electrospinning. The TiO2 NFs were coated by atomic layer deposition (ALD) to grow boron nitride (BN) and palladium (Pd) on their surface. The UV-Vis spectroscopy measurements confirmed the increase of the band gap and the extension of the spectral response to the visible range. The obtained TiO2 /BN/Pd nanofibers were then tested for photocatalysis, and showed a drastic increase of acetaminophen (ACT) degradation (>90%), compared to only 20% degradation obtained with pure TiO2 after 4 h of visible light irradiation. The high photocatalytic activity was attributed to the good dispersion of Pd NPs on TiO2 –BN nanofibers, leading to a higher transfer of photoexcited hole carriers and a decrease of photogenerated electron–charge recombination. To confirm its reusability, recycling tests on the hybrid photocatalyst TiO2 /BN/Pd have been performed, showing a good stability over 5 cycles under UV and visible light. In addition, toxicity tests as well as quenching tests were carried out to check the toxicity of the byproducts formed and to determine active species responsible for the degradation. The results presented in this work demonstrate the potential of TiO2 /BN/Pd nanomaterials, and open new prospects for the preparation of tunable photocatalysts.